Kemahiran berfikir kritis melalui permainan digital dalam persekitaran pembelajaran konstruktivisme sosial - Madjapuni, Mad Noor (Global Academic Excellence, 2019)
The process of implementation of the educational transformation requires a new approach and strategy so that each student can afford to own and master the skills required in the 21st century. Therefore to ensure the development of creativity of educators, methods and strategies of teaching and learning undertaken should take into account the tendencies, abilities and capability maturity of students and be able to think at the level is higher. The increase in popularity is the use of computer technology and communication in human daily life especially in the simulation and digital games have attracted the interest of researchers-researchers to mendalaminya that can increase the capacity and fostering critical thinking skills among students. This concept paper discusses the potential use of digital game toward critical thinking skills of students through social constructivism learning environment.